(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Urethral catheterization is done as a routine procedure in cesarean section. It is associated with great discomfort, high incidence of urinary tract infection, delayed ambulation and longer hospital stay. Objectives: To determine the feasibility and safety of cesarean section without urethral catheterization. Materials and Methods: A prospective, observational study was carried out from April 2012 to March 2013, in the Department of Obstetrics and Gynaecology, CMH Dhaka and IBN Sina Hospital Dhaka among 65 patients who had undergone cesarean section without catheterization. There were some limitations of this study. We had excluded previous cesarean from our study, so the results of this study cannot be generalized. Results: Firs void discomfort was not significantly associated without the use of indwelling catheter. Hospital stay was shorter (94% was discharged on 3rd post operative day). None of the patients had bladder injury. Mean duration of surgery was 45 minutes (44%) and ambulation time 11-14 hours (60%). Average estimated blood loss was 500 ml (41%) and time of 1st voiding was 5-8 hrs (58%). Need for catheterization was significantly low (3%). Conclusion: Cesarean section can be done safely without urethral catheterization with reduced morbidities. Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 3-6